Analysis of Concrete Subsurface Cracks Using Elastic R-Wave Method - Aw, Samantha Jia Ying (2021)
Concrete often plays a vital role in the construction industry. The usage of concrete ranges typically from buildings, pavements, retaining walls, bridges, and other structures. The concrete’s tensile strength is only 10 % of its compressive strength. Thus, the reinforcement bar is introduced to resolve the low tensile strength characteristics of concrete. The subsurface cracks will form due to the corrosion of steel reinforcement. It will continue to propagate and creating a horizontal crack in the concrete. The formation of subsurface crack is not visible, and it will cause a sudden collapse of a structure. It is essential to detect the concrete’s crack and carry out appropriate action or repair to avoid the sudden collapse. The formation of crack will accelerate water and chemical substance penetration into the concrete and decrease the concrete’s strength. The non-destructive test (NDT) is a method that can carry out to examine the properties of a material without damaging it. Thus, Rayleigh wave-based noncontact method was adopted to study the correlations of Rayleigh wave properties on the concrete subsurface cracks. In this research study, 104 cases were conducted to analyze the concrete subsurface cracks with different diameters, the different depth, and the Rayleigh wave generated varies using different sizes of steel ball diameter.